Structural benefits of using carbon nanotube reinforced high-strength lightweight concrete beams - Se-Hee Hong; Jin-Seok Choi; Sun-Jae Yoo; Young-Soo Yoon (Developments in the Built Environment, 2023)
Recently interest in lightweight concrete (LWC) has increased for its cost effectiveness and design reduction, however it has low resistance to external forces. Carbon nanotube (CNT) was incorporated to overcome this disadvantage and achieve high-strength in LWC. The structural response of CNT reinforced high-strength lightweight concrete (HSLC) beams was investigated considering specimen size, tensile reinforcement ratio, and stirrup spacing. As the tensile reinforcement ratio increased from 0.008 to 0.019, yielding and peak load of specimens improved by 92% and 73%, respectively. Interestingly, nanocrack bridging induced by CNT increased the ductility index of reinforced HSLC beams compared to conventional reinforced HSC and LWC beams in the low longitudinal reinforcement index range. At the end, a flexural design model for CNT reinforced HSLC beams was proposed and validated. This study aims to reinforce feasibility by providing both a basic reference for structural response and a cost analysis of CNT reinforced HSLC.